First report of coinfection and whole‐genome sequencing of norovirus and sapovirus in an acute gastroenteritis patient from Pakistan. Issue 2 (10th January 2023) - Umair, Massab; Rehman, Zaira; Haider, Syed Adnan; Usman, Muhammad; Rana, Muhammad Suleman; Ikram, Aamer; Salman, Muhammad
Abstract: Acute gastroenteritis is one of the most common diseases in infants and children in developing countries including Pakistan. In Pakistan, rotavirus (RVA) is known to contribute significantly to pediatric diarrheal illness, but the contribution of other viruses is still unclear. In the current study we have identified a case of mixed infection of norovirus (NoV) and sapovirus (SaV) in a 2‐year‐old child with acute gastroenteritis. The sample was initially processed for the detection of group A RVA through ELISA followed by NoV using RT‐PCR assay. The sample tested positive for NoV RNA and was later subjected to whole‐genome sequencing using meta‐genome approach on Miseq (Illumina) platform. Sequencing results revealed GII.15 genotype of NoV that clustered with viruses from China and USA from 2017 to 2021. We also retrieved the complete genome of SaV (GI.1 genotype) from the same sample and phylogenetic analysis showed clustering with strains reported from Japan, South Korea, US, and Taiwan during 2012−2016. This is the first report from Pakistan that confirms coinfection of NoV and SaV and elucidates their whole genomes. We recommend initiation of NoV and SaV surveillance program to ascertain disease burden and explore genetic diversity, especially as RVA vaccines have been included in national immunization program.